The view of technological innovation in coal industry under the vision of carbon neutralization - Li, Quansheng (International journal of coal science & technology, 2021)
This paper analyzed the current situation and development trends of energy consumption and carbon emissions, and the current situation and development trend of coal consumption in China. In the context of recently established carbon peak and carbon neutralization targets, this paper put forward the main problems associated with the green and low-carbon development and utilization of coal. Five key technological innovation directions in mining were proposed, including green coal development, intelligent and efficient mining, low-carbon utilization and conversion of coal, energy conservation and emission reduction, carbon capture, utilization and storage (CCUS). Focusing on the above technological innovation directions, it is suggested to carry out three basic theories, including the theory of green efficient intelligent mining, clean and low-carbon utilization and transformation of coal, and CCUS. Meanwhile, it is proposed to develop 12 key technologies, including green coal mining and ecological environment protection, efficient coal mining and intelligent mine construction, key technologies and equipment for efficient coal processing, underground coal gasification and mining, ultra-high parameter and ultra-supercritical power generation technology, intelligent and flexible coal-fired power generation technology, new power cycle coal-fired power generation technology, the development of coal-based special fuels, coal-based bulk and specialty chemicals, energy conservation and consumption reduction, large-scale and low-cost carbon capture, CO 2 utilization and storage. Finally, necessary measures from the governmental perspective were also proposed.